Family functioning and academic performance in the school of Education and Human Sciences in a private university - Quinteros Zúñiga, Dámaris S. (Universidad Femenina del Sagrado Corazón, 2018)
The present research aims to study the relationship between family functioning and academic performancevariables of first and second term students of the Faculty of Education and Human Science in a private university.The MacMaster Model of Family Functioning (MMFF) described by Epstein, Baldwing and Bishop (19983)was used in this study. The model identifies seven dimensions on family functioning: problem solving, rolefunctioning, communication, affective responsiveness, affective involvement, behavioral control and generalfunctioning. The Family Assessment Device (FAD) scale based on the McMaster Model of Family Functioning(MMFF) was used for assesing family functioning dimensions. The academic performance average’s indicatorwas obtained from the student’s grades during the first term of studies in 2008.The relationship among every dimension and the academic performance on a sample of 193 students wasanalyzed, in which the families of the students with high academic performance are more functional in almostall dimensions, except the one related to the role functioning. Therefore, the family functioning level has asignificant relationship with the academic performance in the first and second term students of the School ofEducation and Human Sciences, with the exception of the role functioning dimension in which a significantcorrelationship was not found.